Patients with volume-loaded right ventricle - quantification of left ventricular hemodynamic response to intervention measured by noninvasive pressure-volume loops - Sjöberg, Pia; Stephensen, Sigurdur; Arheden, Håkan; Heiberg, Einar; Carlsson, Marcus (Frontiers in Physiology, 2023)
Volume loading of the right ventricle (RV) in patients with atrial septal defect (ASD) and patients with repaired Tetralogy of Fallot (rToF) affects the pumping mechanics of the left ventricle (LV). Intervention of the lesion will relieve the RV volume load however quantifiable impact on exercise capacity, arrhytmias or death are limited. A possible explanation could be remaining effects on the function of the LV. The aim of this study was therefore to investigate if hemodynamics of the LV differs between patients with RV volume load due to ASD or rToF and healthy controls and if they change after intervention. Eighteen patients with ASD, 17 patients with rToF and 16 healthy controls underwent cardiac magnetic resonance imaging (CMR) and maximal exercise test with continuous gas analysis. Reexamination was performed 13 ± 2 months after closure of the ASD in 13 of the patients and 10 ± 4 months after pulmonary valve replacement (PVR) in 9 of the patients with rToF. Non-invasive PV-loops from CMR and brachial pressures were analyzed. Stroke work (SW) and potential energy (PE) increased after ASD closure but not in ToF patients after valve repair. Patients with ASD or rToF had higher contractility and arterial elastance than controls. No major effects were seen in LV energetics or in peak VO2 after ASD closure or PVR. Peak VO2 correlated positively with SW and PE in patients with ASD (r = 0.54, p < 0.05; r = 0.61, p < 0.01) and controls (r = 0.72, p < 0.01; r = 0.53, p < 0.05) to approximately the same degree as peak VO2 and end-diastolic volume (EDV) or end-systolic volume (ESV). In ToF patients there was no correlation between PV loop parameters and peak VO2 even if correlation was found between peak VO2 and EDV or ESV. In conclusion, the LV seems to adapt its pumping according to anatomic circumstances without losing efficiency, however there are indications of persistent vascular dysfunction, expressed as high arterial elastance, which might have impact on exercise performance and prognosis. Future studies might elucidate if the duration of RV volume load and decreased LV filling have any impact on the ability of the vascular function to normalize after ASD closure or PVR.